ElderCare Monitor Application Design: Elderly Health Monitoring based on Family and Community Health Center Collaboration - Wa Ode Tanti; Sri Kusumadewi; Rahadian Kurniawan (Department of Informatics Engineering, Universitas Muhammadiyah Purwokerto, 2025)
The elderly are a vulnerable group that is susceptible to various degenerative diseases. The lack of information and understanding of the elderly causes a high rate of disease complications. This study aims to design an ElderCare Monitor application that is easy to use and tailored to the needs of users. The application caters to a variety of users, including elderly families, the elderly themselves, the pre-elderly, and health center officers. Health workers at the health center and the elderly's family collaborate to independently monitor the health of the elderly and pre-elderly. The system is designed using the design thinking method. The design thinking method involves five stages: empathy, define, ideate, prototyping, and testing. The results of the study showed an effectiveness rate of 95.24% for the elderly and families and 95.83% for health center officers. The average SUS score for families and the elderly was 74.17, while for medical personnel, it was 77.5. Therefore, the ElderCare application received the